Homozygous 6-bp deletion of IGFALS in a prepubertal boy with short stature - Hibiki Doi; Ikuko Kageyama; Yuko Katoh-Fukui; Atsushi Hattori; Maki Fukami; Naoto Shimura (Human Genome Variation)
Abstract Biallelic IGFALS variants lead to acid‒labile subunit (ALS) deficiency characterized by growth hormone resistance with or without delayed puberty. Here, we report a prepubertal boy with a homozygous 2-amino acid deletion within the fourth N-glycosylation motif (c.1103_1108del, p.N368_S370delinsT) associated with parental consanguinity. He showed short stature consistent with ALS deficiency. This case expands the mutation spectrum of IGFALS to include the elimination of only one N-glycosylation motif of ALS.